Case Report: A rare case of mixed medullary-papillary thyroid carcinoma with mixed lymph node metastasis - Yang, De-shi; He, Jing (Frontiers in Oncology, 2025)
IntroductionBy reviewing the diagnosis and treatment process of a rare case of mixed medullary-papillary thyroid carcinoma (MMPTC) in the right lobe, medullary thyroid carcinoma (MTC) combined with papillary thyroid carcinoma (PTC) in the left lobe, and multiple MTCs in the isthmus with mixed lymph node metastasis, we systematically analyzed its pathological features and immunophenotype.Case presentationA 65-year-old Han male patient was found to have a hypoechoic nodule(TI-RADS category 5) in the right lobe of the thyroid gland during a physical examination. Additionally, enlarged lymph nodes were found in the right neck, accompanied by structural abnormalities (The morphology is regular, with a distinct boundary. The internal echo is heterogeneous, presenting anechoic areas and punctate hyperechoic foci. The lymph hilar structure is poorly visualized. Color Doppler Flow Imaging (CDFI) reveals punctate blood flow signals within and surrounding the lesion.). Serum calcitonin (CT), carcinoembryonic antigen (CEA), and thyroglobulin (TG) were all elevated. Subsequently, fine-needle aspiration cytology (FNAC) was performed on the right lobe thyroid mass and a biopsy was taken from the right cervical lymph nodes. The FNAC results indicated that the right lobe thyroid mass was suggestive of MTC. Meanwhile, metastatic PTC was found in the right cervical lymph node biopsy tissue.The patient subsequently underwent a total thyroidectomy combined with radical lymph node dissection in the thyroid and maxillofacial surgery department. The postoperative radical specimen showed that cancer foci were visible in the left lobe, isthmus and right lobe of the thyroid. Among them, a focus of MMPTC was found in the right lobe of the thyroid gland, with the tumor mainly composed of MTC components; in the left lobe, a coexisting lesion of PTC and MTC was found, the two foci are separated by normal thyroid tissue. Two foci of MTC were found in the isthmus of the thyroid gland. A total of 88 lymph nodes were dissected, among which 21 were found to have cancer metastasis. Postoperative serum CEA dropped to the normal level, and CT showed a significant decrease compared with that before the operation.ConclusionsThe peculiarity of this case lies in the fact that preoperative serological tests showed abnormally elevated levels of CT, CEA and TG. FNAC of the right lobe of the thyroid indicated MTC, but at the same time, the puncture of cervical lymph nodes revealed the presence of PTC components. In such a situation, the possibility of coexistence of MTC and PTC should be highly suspected. A standardized surgical treatment plan should be selected, and during the pathological examination, standardized sampling and meticulous reading of the slides should be emphasized, combined with immunohistochemical detection, to reduce the risk of missed diagnosis, provide accurate pathological diagnosis, and thereby offer reliable basis for the formulation of postoperative treatment strategies and prognosis assessment.